Detection of Structural Control on Formation Water Quality, in Hemrin Oilfield, northern Iraq, Using Lineament Analysis and Hydrochemical Data - Faraj Ahmed Al-Sulaiman; Sameer Shaker Abbas Al Fahdawi; Sabbar Abdullah Saleh Al Qaisy (Tikrit Journal of Pure Science)
Formation water analyses of Tertiary reservoir (Euphrates, Jeribe, and Dhiban formations) in Hemrin oilfield reflect high salinity variation between Albufudhul, Nukhaila, and Allas domes. The present study suggests that this variation resulted by two reasons, (1) percolation of surface waters (rain water) which lead to devastation of oil type, (2) interaction between water and host rocks. Satellite image and DEM were used to detect the lineaments and morphometric analyses, which interpret the structural control on salinity variation. The main direction of lineaments are NE-SW, which prevailing with subsurface vertical faults between Albufudhul and Nukhaila domes that playing with SE limb of  Albufudhul dome as conduits for percolation of surface water (rainwater), that lead to dilute the salinity and change the formation water properties from Albufudhul to Nukhaila domes, while the present of vertical fault between Nukhaila and Allas dome considered as semi impermeable according to geometry of domes, so Allas dome considered as semi closed system in comparison with Albufudhul and Nukhaila domes, that lead to increase in salinity and change of formation water properties. Formation water is classified as salinity variety water from medium salinity (TDS of 7430 mg/l), to brine, (TDS of 59118 mg/l), of mixed origin from meteoric water and connate water, of variety of pH value (6.75-8.89) from weak acidic to alkaline. Its type is Na-SO4-chloride and anions are ordered as rCl > SO4 > HCO3, whereas cations ordered as rNa > Ca > Mg. This type of water is associated with open system reservoir, influenced by percolation of surface water and consider as bad zone for preservation of hydrocarbon accumulations especially in Albufudhul and north east limb of Nukhaila domes, while Allas dome considered as closed system reservoir, which is a good zone for preservation of hydrocarbon accumulations.